A Bayesian adaptive randomized phase II multicenter trial of bevacizumab with or without vorinostat in adults with recurrent glioblastoma. Issue 10 (13th March 2020) - Puduvalli, Vinay K; Wu, Jing; Yuan, Ying; Armstrong, Terri S; Vera, Elizabeth; Wu, Jimin; Xu, Jihong; Giglio, Pierre; Colman, Howard; Walbert, Tobias; Raizer, Jeffrey; Groves, Morris D; et al.
Abstract: Background: Bevacizumab has promising activity against recurrent glioblastoma (GBM). However, acquired resistance to this agent results in tumor recurrence. We hypothesized that vorinostat, a histone deacetylase (HDAC) inhibitor with anti-angiogenic effects, would prevent acquired resistance to bevacizumab. Methods: This multicenter phase II trial used a Bayesian adaptive design to randomize patients with recurrent GBM to bevacizumab alone or bevacizumab plus vorinostat with the primary endpoint of progression-free survival (PFS) and secondary endpoints of overall survival (OS) and clinical outcomes assessment (MD Anderson Symptom Inventory Brain Tumor module [MDASI-BT]). Eligible patients were adults (≥18 y) with histologically confirmed GBM recurrent after prior radiation therapy, with adequate organ function, KPS ≥60, and no prior bevacizumab or HDAC inhibitors. Results: Ninety patients (bevacizumab + vorinostat: 49, bevacizumab: 41) were enrolled, of whom 74 were evaluable for PFS (bevacizumab + vorinostat: 44, bevacizumab: 30). Median PFS (3.7 vs 3.9 mo, P  = 0.94, hazard ratio [HR] 0.63 [95% CI: 0.38, 1.06, P  = 0.08]), median OS (7.8 vs 9.3 mo, P  = 0.64, HR 0.93 [95% CI: 0.5, 1.6, P  = 0.79]) and clinical benefit were similar between the 2 arms. Toxicity (grade ≥3) in 85 evaluable patients included hypertension ( n =  37), neurological changes ( n =  2), anorexia ( n =  2), infections ( n =  9), wound dehiscence ( n =  2), deep vein thrombosis/pulmonary embolism ( n =  2), and colonic perforation ( n =  1). Conclusions: Bevacizumab combined with vorinostat did not yield improvement in PFS or OS or clinical benefit compared with bevacizumab alone or a clinical benefit in adults with recurrent GBM. This trial is the first to test a Bayesian adaptive design with adaptive randomization and Bayesian continuous monitoring in patients with primary brain tumor and demonstrates the feasibility of using complex Bayesian adaptive design in a multicenter setting.